Assessment of an online management science course. (1st January 2014) - Gupta, Aman; Mau, Ronald R.; Richardson, Tracey M.
Operations research is widely taught in universities around the world and is considered critically important in solving complex organisational problems. With great emphasis on techniques from mathematical sciences including, mathematical modelling, statistical analysis, simulation modelling and others, this subject is considered to be a challenging course to teach and a difficult course for students to learn. Instructors often devise innovative approaches to effectively deliver content. Due to technology advancements and rising demand for flexible learning opportunities, online learning is becoming a preferred mode among today's student, especially adult learners. This paper documents the redevelopment of a graduate level management science course and presents an empirical study in which surveys collected student perceptions pre- and post-redevelopment. The results indicate students find the redeveloped course to be more relevant to current and future career goals and students are more confident in their ability to apply the course concepts to real world problems.